A yeast strain associated to Anopheles mosquitoes produces a toxin able to kill malaria parasites - Valzano, Matteo (Malar J, 2016)
BACKGROUND: Malaria control strategies are focusing on new approaches, such as the symbiotic control, which consists in the use of microbial symbionts to prevent parasite development in the mosquito gut and to block the transmission of the infection to humans. Several microbes, bacteria and fungi, have been proposed for malaria or other mosquito-borne diseases control strategies. Among these, the yeast Wickerhamomyces anomalus has been recently isolated from the gut of Anopheles mosquitoes, where it releases a natural antimicrobial toxin. Interestingly, many environmental strains of W. anomalus exert a wide anti-bacterial/fungal activity and some of these ‘killer’ yeasts are already used in industrial applications as food and feed bio-preservation agents. Since a few studies showed that W. anomalus killer strains have antimicrobial effects also against protozoan parasites, the possible anti-plasmodial activity of the yeast was investigated. METHODS: A yeast killer toxin (KT), purified through combined chromatographic techniques from a W. anomalus strain isolated from the malaria vector Anopheles stephensi, was tested as an effector molecule to target the sporogonic stages of the rodent malaria parasite Plasmodium berghei, in vitro. Giemsa staining was used to detect morphological damages in zygotes/ookinetes after treatment with the KT. Furthermore, the possible mechanism of action of the KT was investigated pre-incubating the protein with castanospermine, an inhibitor of β-glucanase activity. RESULTS: A strong anti-plasmodial effect was observed when the P. berghei sporogonic stages were treated with KT, obtaining an inhibition percentage up to around 90 %. Microscopy analysis revealed several ookinete alterations at morphological and structural level, suggesting the direct implication of the KT-enzymatic activity. Moreover, evidences of the reduction of KT activity upon treatment with castanospermine propose a β-glucanase-mediated activity. CONCLUSION: The results showed the in vitro killing efficacy of a protein produced by a mosquito strain of W. anomalus against malaria parasites. Further studies are required to test the KT activity against the sporogonic stages in vivo, nevertheless this work opens new perspectives for the possible use of killer strains in innovative strategies to impede the development of the malaria parasite in mosquito vectors by the means of microbial symbionts. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-015-1059-7) contains supplementary material, which is available to authorized users.